Views of Carnac: applications of visibility analysis and dynamic visualisation for understanding the Neolithic monuments of southern Brittany - Corinne Roughley; Colin Shell (Internet Archaeology, 2004)
The Neolithic monuments of the Carnac area of southern Brittany are of international importance. However, archaeologists have tended to study the monuments as individual sites, rather than investigating their landscape settings. This is in part because the landscape is difficult to explore in the field. Modern houses and conifer plantations obscure views; earthen structures have been significantly reduced in size, indeed some have been entirely levelled.